Guia prático para avaliação clínica de enfermagem de úlcera de membros inferiores - Silva, Daiana Barbosa da (Universidade do Vale do Rio dos Sinos, 2014)
A leg ulcer is considered a syndrome that is characterized by irregular or circumscribed loss of the integument, which may reach the subcutaneous tissue and other underlying tissues, commonly affects the lower extremities and can be triggered by many factors. Leg ulcers are identified as chronic wounds, considering the long duration of time between the opening and wound healing, plus plenty of recurrence in a short time. AIM: to determine the most effective method of systematic assessment of lower limb ulcers. MATERIAL AND METHODS: A systematic literature review on the basis of data indexed Crochrane, Medline/Pubmed, Lilacs and MedCarib, using the descriptors ulcers, leg ulcers, foot ulcer, protocols , nursing care and diagnosis. The preparation protocol followed the criteria of (GEP- GHC, 2008) Operating Manual of Clinical Guidelines/Protocols Relief of Management Education and Research Hospital Group Conception and Methodology of guides for it Elaboración of atencion y protocols (GOMEZ, 2007). For the analysis of the results was used for the ranking of levels of evidence classification of the Oxford Centre for Evidence Based Medicine and the Classification of the Grading of Recommendations Assessment, Development and Evaluation system strategy. (MECHANICK et al., 2010; DEL MAR; SALISBURY, GLASZIOU, 2010). RESULTS: There were 74 Crochrane Library, 174 in Medline / Pubmed, Lilacs in articles 31 and 7 in MedCarib data. After applying the inclusion and exclusion criteria, in addition to the search filter, 179 articles remained. Articles in duplicate, without the availability of full text, were excluded, as well as after reading the titles and abstracts, leaving only 14 items. The practical guide to the care of the nurses in the clinical assessment of patients with leg ulcers divided into transcendence and vulnerability, magnitude, objective diagnosis: classification of ulcers types of ulcer assessment and perilesional. CONCLUSION: This clinical practice guide involved the detailing of the lower extremity ulcers rating process, seeking to bring together the best practices and scientific evidence in the literature.
Keywords: Úlcera; Úlcera de perna; Úlcera de pé; Protocolos; Cuidados de enfermagem; Diagnóstico; Ulcers; Leg ulcers; Foot ulcer; Protocols; Nursing; Diagnosis; ACCNPQ::Ciências da Saúde::Enfermagem